Postgraduate Supervision Course 3/2023: roles and responsibilities of a supervisor / Dr. Leow Min Hui - Leow, Min Hui (Academy of Language Studies, 2024)
Postgraduate programmes are offered in all Universiti Teknologi MARA (UiTM) campuses around Malaysia. Meanwhile, Institute of Postgraduate Studies (IPSis) has been established for the purpose of administration and management of postgraduate programmes in UiTM. According to university and Malaysian Qualifications Agency (MQA) regulations, UiTM PhD lecturers who intend to supervise postgraduate students must enrol in the Postgraduate Supervision Course starting from 2019. Recently, I participated in a two-day academic research supervision course entitled ‘Effective Postgraduate Supervision’ organised by IPSis. The course offered a deep dive into the process and procedure in supervising postgraduate students as well as to deliver important information regarding the roles and responsibilities of a supervisor. Considering what I have learned from the course, I believe that developing a distinct personality or set of qualities that makes a good supervisor is crucial for all prospective postgraduate supervisors. Terminologically, ‘academic research supervision’ means the academic guide for a student throughout his/her higher degree by research program, which usually includes offering advice or guidance, showing direction, monitoring research progress, and providing necessary feedback or support in a field of research. Throughout the process of advising, coaching, and mentoring, a good supervision should not overlook the human side of the relationship between a supervisor and a student. Abusive(continuous hostile behaviour), ghost (rarely responding to student), or controlling (micro manager who awaits updates on small issues)supervision must be avoided to keep positive human relationships.